Kebakaran Hutan dan Lahan di Pulau Rupat, Riau - Bambang Hero Saharjo; Mar'ie Al Fauzan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Forest and land fires in Riau province generally occur on peatlands. This is due to the large area of ​​peatlands and intensive land conversion. Peat fires result in high PM 2.5 pollutant content, as happened on Rupat Island, Meranti Islands. Rupat Island has a history of repeated cases of forest and land fires in 2015 and 2019. This study aims to analyze the background of the causes of forest and land fires on Rupat Island, Riau Province. The research was carried out through several stages, namely data collection, data processing and data analysis. Forest fires on Rupat Island caused PM 2.5 content in February and March to have values ​​above the PM 2.5 content threshold. Based on the results of the study, it is known that the background causes of forest and land fires on Rupat Island, Riau, are caused by poor canal management, damaged peat conditions and the influence of the arrival of El Nino. This is the cause of the widespread forest and land fires on Rupat Island. Keywords: forest fires, peat land, Rupat island